9z + 10 - 6z = 7 + 2z - 3 gather together z terms on the left 3z + 10 = 7 + 2z - 3 gather integers on the right 3z + 10 = 2z + 4 subtract 2z from each side z + 10 = 4 subtract 10 from each side z = - 6 ----------------check in original equation 9(- 6) + 10 - 6(- 6) = 7 + 2(- 6) - 3 - 54 + 10 + 36 = 7 - 12 - 3 - 8 = - 8 --------------checks
-2z + 3
8x + 9z
4z + 3 = 6 + 2zSubtract 2z from each side of the equation:2z + 3 = 6Subtract 3 from each side:2z = 3Divide each side by 2:z = 3/2 = 1.5
12x-4y+9z+2y =12x-2y+9z
9z+8 = 3z-10 9z-3z = -10-8 6z = -18 z = -3
3x + y + z = 63x - y + 2z = 9y + z = 3y + z = 3y = 3 - z (substitute 3 - z for y into the first equation of the system)3x + y + z = 63x + (3 - z) + z = 63x + 3 = 63x = 3x = 1 (substitute 3 - z for y and 1 for x into the second equation of the system)3x - y + 2z = 93(1) - (3 - z) + 2z = 93 - 3 + z + 2z = 93z = 9z = 3 (which yields y = 0)y = 3 - z = 3 - 3 = 0So that solution of the system of the equations is x = 1, y = 0, and z = 3.
3-5z
3(3z + 4)
z2 + 9z + 18 = z2 + 6z + 3z + 18 = z(z+6) + 3(z+6) = (z+6)*(z+3)
It is 20z-18 when simplified
4z + 2 + 5z - 3 = 9z - 1